“Філософія політики” в поемі І. Франка “Мойсей” (інтертекстуальний аспект) - Сухомлин, Євгенія; Sukhomlyn, Yevgenia (Волинський національний університет імені Лесі Українки, 2009)
У статті розглядається інтеграція творчості публіциста і митця. Розкривається франківське трактування біблійного міфу про Мойсея: необмежена влада перетворює вождя на фараона; довголітнє очікування народних мас на здійснення владних обіцянок виливається у протест; “сила духа” народу при “гомоні волі” сприяє революції. The article presents the integration of creative work of the publicist and the artist. It is disclosed the Bible interpretation of the myth about Moses. The unlimited power transformed the chief into the pharaoh. The longterm expectation of the people for fulfilling their demands by the power body led to the protest. “The power of spirit” of the nation and “The sound of freedom” favor the revolution.
“The Philosophy of Politics” in the Ivan Franko Poem “Moses”(Intertextual Aspect)
Keywords: інтеграція; вождівство; народ; мислитель; Integration; leadership; people; thinker